PENGARUH KOMUNIKASI MOTIVASI DAN KECERDASAN EMOSIONAL TERHADAP KINERJAPERAWAT RAWATINAP - Lutfi Octafianto, 09.05.51.0024 (Students Journal of Economic and Management, 2013)
The job-performance of Dr. Soewondo kendal hospitalâs nurse is low,because there are any complain from patient to their work and this observation to conect between job-performance dependent variable (Y) to independent variable communication , motivation (X2), and emotional intellegancy (X3).The aim of this observation is to analyse the effect between communication, motivation, and emotional intellegancy to work of Dr. Soewondo kendal hospitalâs nurse. The sample of observation are one hundred nurse of Dr. Sowondo kendal hospital. The method of collecting data is simple random sampling, and the method of analyse data is multyple linier regression analysis which used the help of SPSS program.The result of hypothesis show that communication variable (X1) have positif effect to the job-performance of the nurse. Motivation variable (X2) have positif effect to the job-performance of the nurse. And emotional intellegeancy variable (X3) also have positif effect to the job-performance of the nurse. have on the observation, motivation variable have the most positif effect between the others and value of t is 6,307. The number value is (0,668) show that the ability of independent variable (communication, motivation, and emotional intellegancy) to explain dependent variable (the job-performance of the nurse) is good enough. And the weakness of this observation canât work effectifly if it doing for while, it should be done for a long time to get the best result.Keyword : communication, motivation, emotional intellegancy and job-performance.